2017
DOI: 10.1002/aic.16032
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐cation LiCa‐LSX zeolite with minimum lithium for air separation

Abstract: The aim of this work was to reduce/minimize Li in Li-LSX by replacing the 70% Li 1 cations in Li-LSX that are bonded to the interior or inaccessible sites which are not used for adsorption. Thus, mixed-cation LiCa-LSX containing minimum lithium were prepared by exchanging small fractions of Li 1 into Ca-LSX, followed by dehydration under mild conditions to avoid migration/equilibration of Li cations. Comparisons of adsorption isotherms of N 2 /O 2 and heats of adsorption for the LiCa-LSX samples with that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…As a typical X type of FAU, 13X (Na‐X) exhibits a good N 2 /O 2 separation performance because of the interaction between the quadrupole moment of N 2 and the Na + that is attached to the zeolite framework, and also the suitable cages. [ 5 ] Compared to 13X, Li‐LSX (Lithium type low silicon X type zeolite molecular sieve) exhibits better air separation yields, [ 6 ] the higher N 2 adsorption and N 2 /O 2 selectivity of this material is due to the stronger interactions benefit from the larger quadrupole moment of N 2 compared to that of O 2 (−1.4 D Å for N 2 vs −0.4 D Å for O 2 ) within lithium‐containing molecular sieve channels. [ 7 ] However, the O 2 production efficiency of Li‐LSX has been already reached the limit because of the fixed structure of the X‐type molecular sieve constructed with Si, O, and Al, as the main framework, and the inaccurately controlled loading and distribution of Li.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical X type of FAU, 13X (Na‐X) exhibits a good N 2 /O 2 separation performance because of the interaction between the quadrupole moment of N 2 and the Na + that is attached to the zeolite framework, and also the suitable cages. [ 5 ] Compared to 13X, Li‐LSX (Lithium type low silicon X type zeolite molecular sieve) exhibits better air separation yields, [ 6 ] the higher N 2 adsorption and N 2 /O 2 selectivity of this material is due to the stronger interactions benefit from the larger quadrupole moment of N 2 compared to that of O 2 (−1.4 D Å for N 2 vs −0.4 D Å for O 2 ) within lithium‐containing molecular sieve channels. [ 7 ] However, the O 2 production efficiency of Li‐LSX has been already reached the limit because of the fixed structure of the X‐type molecular sieve constructed with Si, O, and Al, as the main framework, and the inaccurately controlled loading and distribution of Li.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites find widespread use as adsorbents in a range of commercially-important gas separations involving small molecules, including air separation (where N 2 /O 2 selectivity is required) and hydrogen purification (CO 2 /H 2 ). [1][2][3] Furthermore, advanced materials and chemical engineering research continues to drive improved performance in these and similar applications, [4] and also in CO 2 adsorption in natural gas and biogas upgrading (CO 2 /CH 4 ) [5,6] and carbon capture from power plant and industrial emissions (CO 2 /N 2 and CO 2 /CO,H 2 ). [7,8] The performance of zeolites in gas separation relates directly to their high chemical and thermal stability and also to their structural features: high internal surface area accessible via well-defined pores and the presence of extra-framework cations.…”
Section: Introductionmentioning
confidence: 99%
“…These cations affect their adsorption properties in a number of ways. First, the direct cation‐adsorbate interaction enables molecules to be differentiated based on their dipole moment or polarizability – cationic zeolites can separate N 2 from O 2 due to its higher polarizability, for example [1,2] . Extra‐framework cations can also control the effective pore size, if they are located close to windows, as shown by the increasing pore size of K‐, Na‐ and Ca‐forms of zeolite Linde A (known as 3A, 4A, and 5A respectively).…”
Section: Introductionmentioning
confidence: 99%
“…It is very effective to study gas separation by numerical simulation [22][23][24][25][26]. However, most of the studies are based on the 1-D or 2-D RFA [27], and few studies have been reported in research of PSA oxygen production based on 3-D RFA.…”
Section: Introductionmentioning
confidence: 99%